New elements for the definition of possible facies in the Bronze Age Liguria - Laura Sanna (IpoTESI di Preistoria, 2020)
This paper deals with the study of one of the most interesting coastal sites of the entire region of Liguria, the Marine Cave of Bergeggi (Savona). The parts of the site that were visible above water were discovered in the 19th century and its submerged parts in the 1970s. The site underwent several specific investigations over the years, but was never investigated with a systematic strategy. Between January and December 2014, the author of this article had the possibility to examine both the emerged and submerged parts of this cave, which yielded important information about the geomorphological evolution of the site, as well as to propose new interpretations about its human occupation and use, dating at least from the Middle Palaeolithic up to the Iron Age. Concerning the Bronze Age, the author had the possibility to examine in the same period the ceramic collections of the Marine Cave of Bergeggi at the “Paolo Graziosi Museum” in Florence, consisting of material from different research campaigns held between the last quarter of the 19th century and the 1950s. This allowed her to discern cultural parallels between this Ligurian site and some other Italian and French sites. More in detail, it has been possible to shed light on a possible link between the Western Ligurian area and the Eastern Provence. Even if the number of sherds pertaining to the last phases of the Bronze Age and the beginning of the Iron Age from this collection does not seem to be enough to guarantee a proper analysis of this phenomenon, the recognition of some parallels is considered more than a causal connection. Some of the recognised decorations, among which the incised cross of a bottom in the form of a ring, as well as some particular shapes, all found in the Modigliani Gallery at Bergeggi, seem to draw a direct parallel with forms and decorations discovered in some sites of the Eastern Provence area, especially with the site of the Grotte du Chateau in Nice. This existing correspondence, together with other elements, seems to confirm the idea of a relation between these two areas during the Late Bronze Age - Early Iron Age, probably linked to a maritime route. Unfortunately, the shortage of data coming from sites dating to this period, particularly for the Ligurian area, represents a great hurdle for the correct understanding of this relationship, as well as for the analysis of the population dynamics of the coastal part of this region during the Bronze Age. However, up to now, the site of the Marine Cave of Bergeggi, thanks to its particular geomorphological structure, archaeological record and its geographical position linked to the sea and the Val Bormida route can be considered an interesting starting point for a deeper investigation of the probable coastal Ligurian-Provencal connection at the end of the Bronze Age.